Pola Distribusi Spasial Dan Temporal Spesies Lebtobrama Sp. Dengan Menggunakan Teknologi Citra Satelit Aqua Modis Di Perairan Distrik Naukenjerai Kabupaten Merauke. - Marius Agustinus Welliken; Edy H.P Melmambessy (Cenderawasih University, 2023)
This study aims to determine the spatial and temporal variations of chlorophyll-a and SST by using fashionable satellite data in Naukenjerai District waters and the correlation of chlorophyll-a and SST to the distribution of species Lebtobrama Sp. in the Naukenjerai District. This research was conducted in May to June 2022 in the waters of the Naukenjerai District. MODIS image data analysis was performed at the Aquatic Resources Management Laboratory. The data used are data on the catch and the coordinates of the catch from May to June 2022. The results of this study indicate that the distribution of species Lebtobrama Sp. catches from May to June was 857 kg for 12 trips. While the range of chlorophyll-a in May to June ranged from 0.3 mg /m³ - 2.28 mg/m³ and the SPL range from May to June ranged between 25.42°C - 28.42°C. The results of the correlation between chlorophyll-a and species Lebtobrama Sp. catches showed a moderate relationship (correlation coefficient (r) 0.48), while the relationship between SPL and species Lebtobrama Sp. catches showed a strong relationship (correlation coefficient (r) 0.58) and the relationship of chlorophyll-a and SPL with the trapped catch shows a strong relationship (correlation coefficient (r) 0.59).